Prolonged Treatment Duration is Required for Successful Helicobacter pylori Eradication with Proton Pump Inhibitor Triple Therapy in Canada - Carlo A Fallone; Alan N Barkun; Andrew Szilagyi; Karl M Herba; Maida Sewitch; Myriam Martel; Stefanie S Fallone (Canadian Journal of Gastroenterology)
BACKGROUND: Traditional seven-day proton pump inhibitor triple therapy for Helicobacter pylori eradication has recently shown disappointing results outside of Canada. Prolonging therapy may be associated with poorer compliance and, hence, may not have a better outcome in a real-world setting.